Serum levels of monocyte chemoattractant protein-1 has no correlation with gender and age in polytrauma - Balogun, Mosimabale; Odeyemi, Olubunmi; Oyewole, Olugboyega; Ogunrewo, Tolulope; Omoyeni, Richard (International Journal of Research in Orthopaedics, 2022)
Background: Trauma is one of the commonest causes of death among young people with significant increase in morbidity and mortality. Following injuries to tissues, the body responds in an attempt to cause repair of the damaged tissue. Although its significance depends on the interplay of various factors involving neurohormonal and immune responses. Monocyte chemoattractant protein-1 (MCP-1) is a pro-inflammatory chemoattractant produced by the monocyte and causes the further release of chemokines and cytokines needed at the site of tissue injury. It therefore plays a critical role in tissue healing. Methods: This was a prospective hospital-based study carried out at University College Hospital (UCH), Ibadan. Polytrauma patients admitted through the accident and emergency department that met a defined criteria were recruited and had their blood samples taken into an endotoxin free test tube at 48±2 hours after trauma. MCP-1 levels in the serum were estimated though the human MCP-1 enzyme-linked immunosorbent assay (ELISA) kit. This process was carried out using the ELISA technique based on the producer’s guide. Results: 110 patients were recruited for the study. There was no significant difference in gender variations in MCP-1 level (t=-0.935, p=0.351). For the male and female variations in MCP-1 levels, it ranges from 10 to 2841 and 22 to 2687 respectively. Likewise, there was no significant relationship in age variations in MCP-1 values (f=0.959, p>0.05). Conclusions: This study demonstrated no correlation between serum level of monocyte chemoattractant protein-1 with age and gender in polytraumatized patient according to age and gender.